PENDAMPINGAN UMKM “KERIPIK MAK RIP” UNTUK PENGUATAN USAHA PRODUKTIF DAN PEMBANGUNAN EKONOMI HIJAU DI DESA KAWAK JEPARA - Nadhifah, Isyfa Fuhrotun; Ali, Ali; Mohammad, Gunawan (Jurnal Abdi Insani, 2025)
Kawak Village in Jepara Regency has significant potential in the local food sector through the production of cassava chips. However, the "Keripik Mak RIP" MSME still faces serious obstacles, such as unhygienic manual production processes, lack of business legality, simple packaging, and limited marketing. These conditions hinder product quality improvement and competitiveness. Comprehensive assistance is needed so that MSMEs can utilize technology, obtain legality, and expand their markets sustainably. The goal of community service activities is to help partners increase productivity, improve management, obtain business legality, and expand market reach to achieve independence and sustainable village economic development. The implementation method focuses on mentoring, training, and the application of appropriate technology. The activities are carried out in five stages: program socialization, design and installation of an automatic chip cutting machine, assistance in processing NIB and PIRT (National Property Right) (PIRT), training to increase human resource capacity (packaging, digital marketing, and financial literacy), and evaluation and monitoring. All stages are carried out in a participatory manner with members of the Keripik Mak Rip MSME, community leaders, and surrounding MSMEs. The program has resulted in various positive changes. The automatic chip cutting machine increases production speed by 3–4 times and produces more uniform and hygienic slices. The MSME successfully obtained a Business License (NIB) and Product Registration Certificate (PIRT), which expanded market access. Training in packaging design, digital marketing, and financial bookkeeping improved managerial and marketing skills, thereby increasing business competitiveness. Evaluations showed that all targets were achieved with high participation and a tangible impact on the village economy. This community service activity addressed the initial objective of strengthening the productive business of the MSME "Keripik Mak RIP" through business legality, technology implementation, and human resource capacity building. This program has proven to increase efficiency, quality, and marketing reach, while simultaneously fostering the independence and entrepreneurial spirit of the Kawak Village community in a sustainable manner